2018
DOI: 10.1016/j.cub.2018.02.032
|View full text |Cite
|
Sign up to set email alerts
|

Live Observation of Two Parallel Membrane Degradation Pathways at Axon Terminals

Abstract: SUMMARY Neurons are highly polarized cells that require continuous turnover of membrane proteins at axon terminals to develop, function, and survive. Yet, it is still unclear whether membrane protein degradation requires transport back to the cell body or whether degradation also occurs locally at the axon terminal, where live observation of sorting and degradation has remained a challenge. Here, we report direct observation of two cargo-specific membrane protein degradation mechanisms at axon terminals based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 65 publications
4
52
0
Order By: Relevance
“…There is evidence that as axons lose the necessity for growth and instead become geared for neurotransmission, there is a change in the type of endosomal recycling machinery present, with a decline in receptor and membrane protein recycling and a shift toward synaptic vesicle recycling (Bonanomi et al, ). Recent evidence suggests that membrane proteins and synaptic vesicle proteins are also degraded through separate pathways in axon terminals, in support of the hypothesis that the machinery for synaptic vesicle turnover is distinct from that which is required for membrane protein turnover (Jin et al, ). Moreover, the development of synapses has recently been associated with regenerative decline (Tedeschi et al, ).…”
Section: Developmental Decline In Axon Transportmentioning
confidence: 78%
“…There is evidence that as axons lose the necessity for growth and instead become geared for neurotransmission, there is a change in the type of endosomal recycling machinery present, with a decline in receptor and membrane protein recycling and a shift toward synaptic vesicle recycling (Bonanomi et al, ). Recent evidence suggests that membrane proteins and synaptic vesicle proteins are also degraded through separate pathways in axon terminals, in support of the hypothesis that the machinery for synaptic vesicle turnover is distinct from that which is required for membrane protein turnover (Jin et al, ). Moreover, the development of synapses has recently been associated with regenerative decline (Tedeschi et al, ).…”
Section: Developmental Decline In Axon Transportmentioning
confidence: 78%
“…7a-c). Previous work in primary vertebrate neuronal culture as well as Drosophila R1-R6 photoreceptors has shown that autophagosomes formed at axon terminals traffic retrogradely to the cell body 29,44 . We therefore analyzed photoreceptor cell bodies and found large Atg8-positive multivesicular bodies containing Syd-1 (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Rab5 (EEs), Rab7 (LEs), and Rab11 (REs) all traffic in vertebrate axons and have been implicated in the control of axon growth and guidance (Falk et al, 2014; Ponomareva et al, 2016; van Bergeijk et al, 2015). Membrane and transmembrane proteins are transported to axon terminals via a Rab11-dependent mechanism whereas Rab5 and Rab7 are involved in local recycling and retrograde transport back to the soma (Jin et al, 2018; Khodosh et al, 2006). In Drosophila , a loss-of-function mutation in Rab5 causes defects in axon elongation in olfactory projection neurons and sensory neurons (Sakuma et al, 2014; Satoh et al, 2008).…”
Section: Discussionmentioning
confidence: 99%